Atención selectiva y moral heroica. El vigor de William James frente a la crisis de Fin de Siècle - Jatuff, José (2020)
“Selective attention and heroic morality. The vigor of William James in the face of the Fin de Siècle crisis”. In the Principles of Psychology William James support an active version of the mind in which the world is the result of selective attention. This phenomena, which is understood as effort of the will, gravitates between the psychological and the moral sphere and is a vigorous proposal that confronts both the determinism of the positive spirit of the time, and the cynical and pessimistic attitudes that follow this vision. We will explain the psychology of vigor, its practical consequences, how this proposal is situated in the fin de siècle crisis and the differences of nuances that occur in relation to later publications. Our goal is to make a contribution to both the understanding of the concept of strenuous mood and the issue of heroism in the thought of the North american philosopher.